Cervical Cancer Screening: An Analysis of Three Large South African Medical Schemes - Willie, Michael; Kabane, Sipho (Golden Ratio of Data in Summary, 2024)
Cervical cancer poses a considerable public health challenge in South Africa, necessitating effective screening programs for early detection and prevention. However, the COVID-19 pandemic has disrupted healthcare services, including cervical cancer screening, posing challenges to disease management efforts. This study aimed to assess cervical cancer incidence and screening practices among beneficiaries within three major South African medical schemes, analysing trends from 2017 to 2022. Retrospective data were collected to evaluate incidence rates and screening coverage, considering the impact of the pandemic. Screening coverage declined during the epidemic, recovering in 2021 but declining again in 2022. Different health plans showed a more than forty per cent fall in cervical cancer screening rates between 2021 and 2022, with 2022 having the lowest level, even lower than the COVID-19 era. The trends indicate COVID-19 interruptions have a negative impact post-COVID-19. Recommendations include targeted outreach, telemedicine options, and strengthened collaboration to enhance screening programs and mitigate pandemic-related disruptions. This study contributes valuable insights into cervical cancer management, highlighting the need for proactive measures to ensure the continuity of essential healthcare interventions amid public health emergencies.